Bio-inspired CO2 conversion by iron sulfide catalysts under sustainable conditions. Issue 35 (2nd April 2015) - Roldan, A.; Hollingsworth, N.; Roffey, A.; Islam, H.-U.; Goodall, J. B. M.; Catlow, C. R. A.; Darr, J. A.; Bras, W.; Sankar, G.; Holt, K. B.; Hogarth, G.; de Leeuw, N. H.
Abstract : CO2 conversion to small bio-molecules on greigite minerals under room temperature and pressure. Abstract : The mineral greigite presents similar surface structures to the active sites found in many modern-day enzymes. We show that particles of greigite can reduce CO2 under ambient conditions into chemicals such as methanol, formic, acetic and pyruvic acid. Our results also lend support to the Origin of Life theory on alkaline hydrothermal vents.